BIMTEKS PENGEMBANGAN SOAL AKM NUMERASI BAGI GURU DI PONPES TAZAKKA KABUPATEN MURATARA - Drajat Friansah; Yufitri Yanto (LP4MK STKIP PGRI Lubuklinggau, 2023)
The results of the 2021 National Assessment state that 2 out of 3 students have not achieved minimum competencies and there is a competency gap between students in Java and outside Java. One of the efforts in solving problems that occur is through technical guidance activities for teachers to develop AKM questions. This service aims to provide assistance in the development of AKM questions for teachers in the North Tazakka Musi Rawas Islamic Boarding School. The scope of development activities regarding AKM in the numeracy aspect. The methods used include: 1) initial evaluation stage, 2) enrichment stage, 3) technical guidance stage, 4) mentoring stage, and 5) final evaluation stage. As a result of this service, participants have knowledge about cognitive levels, domain content and learning progression of AKM Numeracy as well as artifacts of activity participants in the form of AKM Numeracy questions.